Analisis Kualitas Pelayanan pada Bank BTN di Kota Bandung - Rahmatullah, Muhammad Yunus; Suhaeni, Tintin (Applied Business and Administration Journal, 2022)
Banks are financial institutions that focus on services, therefore in order to flourish in the highly competitive banking industry, they must deliver the greatest service to their consumers. To be able to survive or even excel in the increasingly fierce banking competition, every bank must be able to develop the best quality of service for its customers. Bank BTN, also known as PT. Bank Tabungan Negara (Persero) Tbk, is one of the largest state-owned banks in Indonesia. However, while conducting business, Bank BTN received numerous consumer complaints over the quality of services offered. Complaints submitted by customers range from long queues until employees are not friendly in serving customers. This study aims to assess the service quality of Bank BTN in Bandung. This study uses the concept of Banking Service Quality (BSQ) which was introduced by Bahia and Nantel in 2000 with 6 (six) dimensions, including effectiveness and assurance, access, price, tangible, service portfolio, and reliability. This study employs descriptive analysis with a quantitative approach as its research methodology. The technique for collecting data consisted of delivering questionnaires to 120 Bank BTN clients in Bandung. Based on the dimensions of effectiveness and assurance, access, price, tangible, service portfolio, and reliability, the outcomes showed that the quality of Bank BTN's services in Bandung meets the criteria for a favorable evaluation. The dimension with the highest value is the effectiveness and assurance dimension, whereas the dimension with the lowest value is the pricing dimension price.